Idiopathic pulmonary fibrosis: a clinical case of long-term follow-up - Galina L. Ignatova; Elena V. Blinova; Maria S. Belsner; Marina A. Korotkaia (ZAO "Consilium Medicum", 2022)
Idiopathic pulmonary fibrosis is a specific form of chronic progressive fibrotic interstitial pneumonia of unknown etiology. Over the past decade, significant progress has been made in developing and utilizing a diagnostic algorithm for patients with idiopathic pulmonary fibrosis, involving analysis of clinical, laboratory, and instrumental data, primarily the results of high-resolution chest computed tomography. Early antifibrotic therapy can alter the disease course, slow its progression, and improve the prognosis.